2013
DOI: 10.1111/tmi.12055
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Can we afford to overlook hand hygiene again?

Abstract: L'accès à l'eau potable et fiable et à l'assainissement, Objectif 7 du Millénaire pour le Développement, cible 7c, est essentiel pour la santé et le bien‐être et est reconnu comme un droit humain. L'hygiène offre de nombreux avantages pour la santé, liés à l'eau et à l'assainissement et pourtant elle est encore absente des Objectifs du Millénaire pour le Développement. En 2013, l'Assemblée Générale des Nations Unies se réunira pour convenir des objectifs et cibles de développement durable postérieurs à 2015. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Moreover, co-infections are largely driven by environmental factors (Lisam and Lisam 2009, Greenland et al 2013, Taye et al 2014) -emphasising the dominance of the virus-environment dynamics during the Asymptomatic period. However, treating co-infections has the effect of increasing the body's immune response to the virus, thus reducing the viral load (Modjarrad et al 2010)which takes us back to the virus-human dynamic.…”
Section: Pattern Management Of the Virus-human-environment Dynamics Amentioning
confidence: 99%
“…Moreover, co-infections are largely driven by environmental factors (Lisam and Lisam 2009, Greenland et al 2013, Taye et al 2014) -emphasising the dominance of the virus-environment dynamics during the Asymptomatic period. However, treating co-infections has the effect of increasing the body's immune response to the virus, thus reducing the viral load (Modjarrad et al 2010)which takes us back to the virus-human dynamic.…”
Section: Pattern Management Of the Virus-human-environment Dynamics Amentioning
confidence: 99%
“…26 There are limited data behind the prevention of pneumonia through WASH interventions, 27 though a recent estimate suggested that hand washing with soap could prevent over 600,000 deaths from diarrhea and pneumonia combined. 28 …”
Section: Public Health Measures For Prevention Of Childhood Pneumoniamentioning
confidence: 99%
“…Katukiza et al (2010) identified the Urine Diverting Dry Toilet (UDDT) and biogas latrines as possible good solutions for a specific urban slum in Uganda, but point out the lack of acceptance of these simple technologies. Furthermore, neither solution represents an integrated option for hand-washing, a necessary element for making any sanitation solution truly hygienic (Greenland et al, 2013). …”
Section: Introductionmentioning
confidence: 99%